Noise sensitivity associated with nonrestorative sleep in Chinese adults: a cross-sectional study - Sha Li; Daniel Yee Tak Fong; Janet Yuen Ha Wong; Bradley McPherson; Esther Yuet Ying Lau; Lixi Huang; Mary Sau Man Ip (BMC, 2021)
Abstract Background Nonrestorative sleep is a common sleep disorder with a prevalence ranging from 1.4 to 35%, and is associated with various psychological and physical health issues. Noise exposure and noise sensitivity have been proposed to contribute to nonrestorative sleep. This study aimed to examine the relationships among noise, noise sensitivity, nonrestorative sleep, and physiological sleep parameters in Chinese adults. Methods A cross-sectional household survey was conducted with randomly selected Chinese adults based on a frame stratified by geographical districts and types of quarters in Hong Kong. We administered a battery of questionnaires, including the Nonrestorative Sleep Scale, the Weinstein Noise Sensitivity Scale, the ENRICHD Social Support Instrument, the Patient Health Questionnaire, and the Perceived Stress Scale to assess nonrestorative sleep, noise sensitivity, social support, somatic symptoms and stress, respectively. Anxiety and depression were evaluated by the Hospital Anxiety and Depression Scale while sociodemographic and lifestyle characteristics were assessed with an investigator-developed sheet. Nocturnal noise level and physiological sleep parameters were measured during nighttime for a week by noise dosimetry and actigraphy, respectively. A structured multiphase linear regression was conducted to estimate associations. Results A total of 500 adults (66.4% female) with an average age of 39 years completed this study. Bivariate regressions showed that age, marital status, occupation, family income, season, exercise, cola and soda consumption, social support, somatic symptoms, stress, depression, noise sensitivity, total sleep time, and awakenings were associated with nonrestorative sleep. In the multivariable analysis, family income, season, exercise, social support, somatic symptoms, stress, and depression remained associated with nonrestorative sleep. Specifically, a one-unit increase of noise sensitivity was associated with 0.08 increase in nonrestorative sleep (95% confidence interval [CI]: 0.01, 0.15, p = 0.023). Nocturnal noise was negatively associated with time in bed (b = − 1.65, 95% CI: − 2.77, − 0.52, p = 0.004), total sleep time (b = − 1.61, 95% CI: − 2.59, − 0.62, p = 0.001), and awakenings (b = − 0.16, 95% CI: − 0.30, − 0.03, p = 0.018), but was not associated with nonrestorative sleep. Conclusions Nonrestorative sleep was predicted by noise sensitivity in addition to family income, season, exercise, social support, somatic symptoms, stress, and depression.